Comparative Analysis of Phylogenetic Assignment of Human and Avian ExPEC and Fecal Commensal Escherichia coli Using the (Previous and Revised) Clermont Phylogenetic Typing Methods and its Impact on Avian Pathogenic Escherichia coli (APEC) Classification - Logue, Catherine M.; Wannemuehler, Yvonne; Nicholson, Bryon A.; Doetkott, Curt; Barbieri, Nicolle L.; Nolan, Lisa K. (Frontiers in Microbiology, 2017)
The Clermont scheme has been used for subtyping of E. coli since it was initially described in early 2000. Since then, researchers have used the scheme to type and sub-type commensal E. coli and pathogenic E. coli, such as extraintestinal pathogenic E. coli (ExPEC), and compare their phylogenetic assignment by pathogenicity, serogroup, distribution among ExPEC of different host species and complement of virulence and resistance traits. Here, we compare assignments of human and avian ExPEC and commensal E. coli using the old and revised Clermont schemes to determine if the new scheme provides a refined snapshot of isolate classification. 1,996 E. coli from human hosts and poultry, including 84 human neonatal meningitis E. coli isolates, 88 human vaginal E. coli, 696 human uropathogenic E. coli, 197 healthy human fecal E. coli, 452 avian pathogenic E. coli (APEC), 200 retail poultry E. coli, 80 crop and gizzard E. coli from healthy poultry at slaughter and 199 fecal E. coli from healthy birds at slaughter. All isolates were subject to phylogenetic analysis using the Clermont (2000) and (2013) schemes and compared to determine the effect of the new classification on strain designation. Most of the isolates’ strain designation remained where they were originally assigned. Greatest designation change occurred in APEC where 53.8% of isolates were reclassified; while classification rates among human strains ranged from 8-14%. However, some significant changes were observed for UPEC associated strains with significant (P<0.05) designation changes observed from A to C and D to E or F phylogenetic types; a similar designation change was noted among NMEC for D to F designation change. Among the APEC significant designation changes were observed from A to C and D to E and F. These studies suggest that the new scheme provides a tighter and more meaningful definition of some ExPEC; while the new typing scheme has a significant impact on APEC classification. A comparison of phylogenetic group assignment by content of virulence, resistance, replicon and pathogenicity island genes in APEC suggests that insertion of pathogenicity islands into the genome appears to correlate closely with revised phylogenetic assignment.